Comparative gene expression responses to Babesia infection and oil contamination in a seabird - Esperanza, Carlos W.; Quock, Rachel C.; Duerr, Rebecca S.; Roy, Scott W.; Sehgal, Ravinder N. M. (Frontiers in Conservation Science, 2024)
The common murre (Uria aalge) is a species of seabird particularly vulnerable to several environmental stressors. Here, we investigated the common murre's transcriptomic responses to the conditions of oil contamination and Babesia infection. Changes in gene expression were characterized using whole transcriptomes assembled from blood samples of naturally infected and environmentally contaminated birds undergoing rehabilitation. 194 shared genes were found to be differentially expressed in response to both parasitic infection and oil contamination. Notable genes were ANXA2, LY96, and LY96, each of which may play a role in the immune response by mediating the production of pro-inflammatory cytokines. Gene Set Enrichment Analysis then determined what biological functions were most affected by each condition. Results showed that infection and contamination both elicited significant changes in expression of genes related to stress response, immune response, and inflammatory response. Expression changes in response to contamination were also related to lipid transport and localization. The large amount of overlap in the gene expression changes to infection and oil contamination may indicate a generalized stress response by the host, and the lipid metabolism response may be specific to contamination. These results provide new insights into the molecular processes involved in the common murre's response to environmental stress and have important implications for the conservation and management of this and other seabird species.